Penguatan Tata Kelola Parawisata Untuk Peningkatan Pendapatan Kecamatan Maitara Selatan Kota Tidore Kepuluan - Fajri Hatim; Musdar Muhammad; Muhammad Kamal (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
From the various tours in the city of Tidore, these islands are expected to contribute to encouraging economic growth and equitable development that causes the welfare of the people in the city of Tidore Islands specifically on Maitara Island. Because tourism can also have a positive impact on economic growth. PKM Method Lectures, Practice and Participant Assistance. PKM results; Sunday, March 19, 2022, took place at the tourist site. The participants who attended this PKM activity were 30 people consisting of village government, community shops and youth shops engaged in tourism development in Ebay village. Good governance is needed, so that all sectors have an economic impact on the community, increasing people's income; Ticket management must be improved, waste is managed to make it an economic value in tourism places make tourism eeducation for visitors, transportation tools are arranged properly so that visitors can reach transportation costs and transportation at any time is always there if needed by visitors to tourism places.